2011
DOI: 10.5539/ijbm.v6n7p261
|View full text |Cite
|
Sign up to set email alerts
|

Examine the Commercialization Research Outcomes in Iran A Structural Equation Model

Abstract: The study presents a structural equation model of commercialization. In this study, reviewing the previous studies conducted on commercialization of research outcomes and a content analysis 33 factors affecting commercialization were extracted and categorized in 6 main groups, namely, research-oriented factors, industry-oriented factors, the government, technology parks and growth centers, environment, and commercialization. Then, based on the identified indicators, the conceptual model of commercializing rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Based on the SLR analysis, it has been identified that firm's orientation plays an important role on the success of innovation commercialization and strategic orientation is the most widely type of firms' orientation studied by researchers. Strategic orientation was categorized as market orientation [66], entrepreneurial orientation ( [10]; [25]; [52]; [57]; [64]), network orientation [64], technological orientation [64], industrial orientation ( [6]; [33]), and research orientation [6].…”
Section: Factors That Affect the Success Of Innovation Commercializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the SLR analysis, it has been identified that firm's orientation plays an important role on the success of innovation commercialization and strategic orientation is the most widely type of firms' orientation studied by researchers. Strategic orientation was categorized as market orientation [66], entrepreneurial orientation ( [10]; [25]; [52]; [57]; [64]), network orientation [64], technological orientation [64], industrial orientation ( [6]; [33]), and research orientation [6].…”
Section: Factors That Affect the Success Of Innovation Commercializationmentioning
confidence: 99%
“…There are few studies apply this variable as moderator [58]; while there were another studies employed it as independent variable meaning that, it has a direct relationship with commercialization performance ( [16]; [53]; [55]; [63]; [90]). According to [37] and [45], the external environment example, capital situation and labor, shaped from government may also influence the innovation market ( [6]; [39]; [56]; [76]).…”
Section: Factors That Affect the Success Of Innovation Commercializationmentioning
confidence: 99%
“…"Technology receiver factor" deals with the adoption /absorption capability of the technology receiver particularly in terms of variables such as top management championing the project [5], [16], [17], having competent team [5], [13], strong financial background [1], [16], [18], prior business experience [1], [15], [19], vision and passion [19] and domain knowledge [8], [19]. "Market factor" primarily addresses the market potential for the product/service in terms of variables such as large market size [6], [19], [20], product meeting user needs [5], [18], [19], product/service having competitive price and quality [5], [6] and first to market [5], [19]. "Financial factor" concerns with the variables such as techno-economic feasibility / variability [9], [21], [22], easy access to finance [1], [5], [9], [20] and longer repayment period of debt [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…"Market factor" primarily addresses the market potential for the product/service in terms of variables such as large market size [6], [19], [20], product meeting user needs [5], [18], [19], product/service having competitive price and quality [5], [6] and first to market [5], [19]. "Financial factor" concerns with the variables such as techno-economic feasibility / variability [9], [21], [22], easy access to finance [1], [5], [9], [20] and longer repayment period of debt [1]. "Government policy factor" concerns with the variables such as pro-active legislative acts [7], [20], [23]; financial incentives from government [1], [24] and strengthening of the existing financial/incubation schemes [1], [24], [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Content analysis is a method confirmed in many studies and is considered as one of the instruments of theoretical frameworks (Kassarjian, 1977;Kolbe & Burnett, 1991;Okazaki & Rivas, 2002;Behboudi et al, 2011). Through content analysis, 34 indicators confirmed by most researchers were identified and categorized in 7 main constructs on the basis of exploratory factor analysis.…”
Section: Conceptual Modelmentioning
confidence: 99%